Mathematics E-Module Based on Problem Based Learning to Improve Problem-Solving Skills of Fifth Grade Elementary School Students - Suryati; Joko Sulianto; Sumarno (Universitas Pendidikan Ganesha, 2025)
Problem-solving ability is one of the abilities that students must have, but this ability is still relatively low. This study aims to produce and test the quality of mathematics learning e-modules based on Problem Based Learning in improving problem-solving abilities. The method used is the Research and Development (R&D) type with the ADDIE model. The subjects of this study were material and media expert validators, teachers, and fifth-grade elementary school students. Data were collected through material and media expert validation questionnaires, practical questionnaires by teachers and students, student response effectiveness questionnaires, and problem-solving ability tests through pretests and posttests. Data analysis techniques used in this study were quantitative and qualitative. The results showed that the development of e-modules based on Problem Based Learning can improve students' problem-solving abilities. The results of expert validation were qualified as very valid, practical validation by teachers and students were qualified as very practical, and student response effectiveness was qualified as very effective. The N-gain value obtained was 0.7288 indicating a high increase in students' problem-solving abilities. So, it can be concluded that the problem-based learning-based mathematics e-module meets the criteria of being valid, practical, and effective in improving fifth-grade elementary school students' problem-solving skills. Consequently, this e-module can be used as an alternative digital teaching material to support technology-based and student-centered mathematics learning in elementary schools.